Modulation of bacterial multicellularity via spatio-specific polysaccharide secretion - Islam, Salim T; Vergara Alvarez, Israel; Saïdi, Fares; Guiseppi, Annick; Vinogradov, Evgeny; Sharma, Gaurav; Espinosa, Leon; Morrone, Castrese; Brasseur, Gael; Guillemot, Jean-François; Benarouche, Anaïs; Bridot, Jean-Luc; et al. (PLoS biology, 2020)
The development of multicellularity is a key evolutionary transition allowing for differentiation of physiological functions across a cell population that confers survival benefits; among unicellular bacteria, this can lead to complex developmental behaviors and the formation of higher-order community structures. Herein, we demonstrate that in the social δ-proteobacterium Myxococcus xanthus, the secretion of a novel biosurfactant polysaccharide (BPS) is spatially modulated within communities, mediating swarm migration as well as the formation of multicellular swarm biofilms and fruiting bodies. BPS is a type IV pilus (T4P)-inhibited acidic polymer built of randomly acetylated β-linked tetrasaccharide repeats. Both BPS and exopolysaccharide (EPS) are produced by dedicated Wzx/Wzy-dependent polysaccharide-assembly pathways distinct from that responsible for spore-coat assembly. While EPS is preferentially produced at the lower-density swarm periphery, BPS production is favored in the higher-density swarm interior; this is consistent with the former being known to stimulate T4P retraction needed for community expansion and a function for the latter in promoting initial cell dispersal. Together, these data reveal the central role of secreted polysaccharides in the intricate behaviors coordinating bacterial multicellularity.